(untitled) (KULT_online, 2023)
Disunion within the Union is a revised study of the author’s article published in the journal of the Ukrainian Research Institute at Harvard University in 1984. Larry Wolff, the leading scholar and historian in the field of eighteenth century Central and Eastern Europe, has decided to return to the subject and enrich his earlier engagement with it with new insights. The result is an engaging study of the history of the Uniate church during the turbulent times of the partitions of the Polish-Lithuanian Commonwealth.